A GIPC1-palmitate switch modulates dopamine drd3 receptor trafficking and signaling - Arango-Lievano, Margarita; Şensoy, Özge; Borie, Amelie; Corbani, Maithe; Guillon, Gilles; Sokoloff, Pierre; Weinstein, Harel; Jeanneteau, Freddy (Amer Soc Microbiology, 2016)
Palmitoylation is involved in several neuropsychiatric and movement disorders for which a dysfunctional signaling of the dopamine D3 receptor (Drd3) is hypothesized. Computational modeling of Drd3's homologue, Drd2, has shed some light on the putative role of palmitoylation as a reversible switch for dopaminergic receptor signaling. Drd3 is presumed to be palmitoylated, based on sequence homology with Drd2, but the functional attributes afforded by Drd3 palmitoylation have not been studied. Since these receptors are major targets of antipsychotic and anti-Parkinsonian drugs, a better characterization of Drd3 signaling and posttranslational modifications, like palmitoylation, may improve the prospects for drug development. Using molecular dynamics simulations, we evaluated in silico how Drd3 palmitoylation could elicit significant remodeling of the C-terminal cytoplasmic domain to expose docking sites for signaling proteins. We tested this model in cellulo by using the interaction of Drd3 with the G-alpha interacting protein (GAIP) C terminus 1 (GIPC1) as a template. From a series of biochemical studies, live imaging, and analyses of mutant proteins, we propose that Drd3 palmitoylation acts as a molecular switch for Drd3-biased signaling via a GIPC1-dependent route, which is likely to affect the mode of action of antipsychotic drugs.
WOS: 000372330700014
PubMed ID: 26787837